Succession and management of tropical dry forests in the Americas: Review and new perspectives - Quesada, Mauricio; Sanchez-Azofeifa, G. Arturo; Alvarez-Anorve, Mariana; Stoner, Kathryn E.; Avila-Cabadilla, Luis; Calvo-Alvarado, Julio; Castillo, Alicia; Espirito-Santo, Mario M.; Fagundes, Marcilio; Fernandes, Geraldo W.; Gamon, John; Lopezaraiza-Mikel, Martha; et al. (Elsevier B.V., 2009)
Understanding tropical forest succession is critical for the development of tropical forest conservation strategies worldwide, given that tropical secondary forests can be considered the forests of the future. Tropical dry forests (TDF) are among the most threatened tropical ecosystems, there are more secondary forests and forest restoration efforts that require a better understanding of successional processes. The main goal of this synthesis for this special issue on the ecology and management of tropical dry forests in the Americas is to present a summarized review of the current knowledge of the ecology and management implications associated to TDF succession. We explore specific issues associated to tropical dry forest succession with emphasis on the use of chronosequences, plant diversity and composition, plant phenology and remote sensing, pollination, and animal-plant interactions; all under the integrating umbrella of ecosystem succession. We also emphasize the need to conduct socio-ecological research to understand changes in land-use history and its effects on succession and forest regeneration of TDF. We close this paper with some thoughts and ideas associated with the strong need for an integrating dimension not considered until today: the role of cyberinfrastructure and eco-informatics as a tool to support sound conservation, management and understanding of TDF in the Americas. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Tropical dry forest; Forest conservation; Forest management; Tropical succession; Plant phenology; Pollination webs; Seed dispersal; Socio-ecosystems; Cyberinfrastructure; Eco-informatics